Postoperative surgical site infection rate in patients with diabetes following Mohs micrographic surgery: a retrospective analysis. (19th February 2022) - Hansen, T.; Gangal, A.; Hijab, E.; Barrett, D.; Yeung, H.; Cao, Y.; Switchenko, J.; Blalock, T.W.
Abstract: Background: Incidence of surgical site infection (SSI) following Mohs micrographic surgery (MMS) amongst patients with diabetes is largely unknown. Objective: Evaluate diabetes as a potential SSI risk factor in MMS by comparing SSI incidence in a cohort of patients with and without diabetes. Methods: A 5‐year retrospective review to determine SSI rate in patients with diabetes compared to patients without diabetes. SSI incidence in patients with diabetes was further compared by A1c, and the impact of antibiotics on SSI rate was also examined. Results: Overall rate of SSI was 1.47% (53/3597 cases). SSI rate amongst patients with diabetes was 1.95% (14/719 cases) compared to 1.35% (39/2878 cases) in patients without diabetes, with a non‐significant odds ratio for SSI of 1.45 (95% CI = 0.78–2.68, P  = 0.241). Multivariable logistic regression analysis revealed no difference in SSI. Stratification of diabetic patients by A1c into ≥7.0 and <7.0 compared to patients without diabetes yielded no statistically significant difference in SSI amongst all groups ( P  = 0.815). Whether an antibiotic was prescribed did not significantly impact SSI rate between groups. Conclusion: No significant difference in postoperative SSI was found in patients with diabetes compared to patients without diabetes following MMS regardless of degree of glycaemic control.